Study On Estimation of Cargo Hold Ship Construction Container 100 TEUS With Mathematical And 3D Modelling Method Autodesk Inventor - Ridho, Mohamad Farizqi; Fadillah, Arif (Institut Teknologi Sepuluh Nopember, 2024)
Estimate the ship’s weight steel is very important before pre-design. This is useful to ensure that the ship's weight does not exceed the basic design requested by the owner. 3D modeling is made in order to shorten the work time and produce a more precise calculation of the weight of the ship compared using mathematical calculations. The study compares the ship weight by using a mathematical method and using the 3D modelling method using autodesk inventor software. The result of the estimation of the weight of the ship’s steel cargo hold construction using 3D modelling method for the block system. It was found that the calculation of the weight of steel using the autodesk inventor method has a fairly good difference with the mathematical method. Calculation with 3D modelling autodesk inventor has a total steel weight of 255,077 tons and 259,868 tons for the mathematical method. The difference in autodesk inventor result is 4,791 tons or 1,84% less than the ship’s weight steel mathematical method. The result of the ship’s steel weight being smaller due to several factor that are not included in 3D modelling and the completeness of drawing, because the more detailed the modeled drawing, will be smaller the difference in the ship’s weight steel produced. Total estimation cost of the modeled cargo holds grandblock with matematical methods Rp.2.235.543.621. while the total cost of using 3D modelling auotdesk inventor Rp.2.298.621..